Optimization of 1.3-μm InGaAsP/InP Electro-Absorption Modulator - Wang, Hui-Tao; Zhou, Dai-Bing; Zhang, Rui-Kang; Lu, Dan; Zhao, Ling-Juan; Zhu, Hong-Liang; Wang, Wei; Ji, Chen (Chinese physics letters, 2015)
We report the simulation and experimental results of 1.3-μm InGaAsP/InP multiple quantum well （MQW） electro-absorption modulators （EAMs）. In this work, the quantum confined Stark effect of the EAM is system- atically analyzed through the finite element method. An optimized structure of the 1.3-μm InGaAsP/InP QW EAM is proposed for applications in 100 G ethernet. Then 1.3-μm InGaAsP/InP EAMs with f-3dB bandwidth of over 20 GHz and extinction ratio over 20 dB at 3 V bias voltage are demonstrated.